2016
DOI: 10.1016/j.aap.2016.08.028
|View full text |Cite
|
Sign up to set email alerts
|

A behavioral economic analysis of texting while driving: Delay discounting processes

Abstract: The purpose of the present study was to examine an impulsive decision-making process underlying texting while driving from a behavioral economic perspective. A sample of 108 college students completed a novel discounting task that presented participants with a hypothetical scenario in which, after receiving a text message while driving, they rated the likelihood of replying to a text message immediately versus waiting to reply for a specific period of time. Participants also completed a delay discounting task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 67 publications
3
28
2
Order By: Relevance
“…With respect to the behavioral measure of impulsivity as assessed by delay discounting of hypothetical monetary rewards, however, the present findings that there was no significant relation between a behavioral measure of impulsivity and the frequency of texting while driving are consistent with Hayashi et al’s (2016) study but inconsistent with Hayashi et al’s (2015) study. It is important to note that when a behavioral measure of impulsivity was assessed by delay discounting of social rewards in Hayashi et al (2016), a significant relation was found between the frequency of texting while driving and the behavioral measure of impulsivity. These inconsistencies between self-reported and behavioral measures of impulsivity, as well as between different types of rewards to be discounted, have been reported in the literature (e.g., Johnson et al, 2015; Malesza and Ostaszewski, 2016).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…With respect to the behavioral measure of impulsivity as assessed by delay discounting of hypothetical monetary rewards, however, the present findings that there was no significant relation between a behavioral measure of impulsivity and the frequency of texting while driving are consistent with Hayashi et al’s (2016) study but inconsistent with Hayashi et al’s (2015) study. It is important to note that when a behavioral measure of impulsivity was assessed by delay discounting of social rewards in Hayashi et al (2016), a significant relation was found between the frequency of texting while driving and the behavioral measure of impulsivity. These inconsistencies between self-reported and behavioral measures of impulsivity, as well as between different types of rewards to be discounted, have been reported in the literature (e.g., Johnson et al, 2015; Malesza and Ostaszewski, 2016).…”
Section: Discussioncontrasting
confidence: 98%
“…They found that students who frequently texted while driving were more impulsive as measured by the delay discounting task. In a subsequent study by Hayashi et al (2016) using a hypothetical texting while driving scenario, impulsivity was measured by delay discounting of both monetary and social rewards (i.e., opportunities to reply to a text message). Consistent with the previous study, students who frequently texted while driving were more impulsive, only with the social reward.…”
Section: Introductionmentioning
confidence: 99%
“…Hayashi, Russo, and Wirth (2015) found that drivers who frequently text while driving were more impulsive, as measured by the degree of delay discounting with hypothetical monetary reinforcers, than those who infrequently text while driving. In a subsequent study, Hayashi, Miller, Foreman, and Wirth (2016) examined whether opportunities to text while driving as a social reinforcer were subject to delay discounting. In a delay-discounting task with a hypothetical scenario, participants rated their likelihood of immediately replying to a text message received while driving versus waiting to reply until arriving at a destination.…”
mentioning
confidence: 99%
“…Finally, the third purpose of the present study was to assess the construct validity of the novel demand task by testing whether a variable known to affect texting while driving, such as delay to a destination (e.g., Hayashi et al, 2016), can affect drivers’ demand for social interaction from texting while driving. In the hypothetical scenarios, two delay conditions were presented: Drivers receive a text message when their arrival to a destination is 15 min or 60 min.…”
mentioning
confidence: 99%
See 1 more Smart Citation